The Relationship between Perception and Satisfaction of Service Quality among Business Students in Polytechnics in Malaysia - Zainal Abidin, Noor Saadah (2008)
This study determines business students’ levels of perceptions of six service quality factors and their relationships to their satisfaction in polytechnics. The factors identified from literature were quality of program, facilities, academic staff, support services, accessibility and location, as well as campus climate. Differences among students’ years, levels of studies, types of sponsorship and zones were determined as well as predictors of students’ satisfaction. The primary data were collected using student survey questionnaires through proportionate cluster sampling. A total of 469 business students were involved in the study sample. Findings indicated ‘moderate’ to ‘good’ levels of satisfaction among students. Significant differences were observed between certificate and diploma students on quality facilities, support services and campus climate. Significance differences were found among students of different years on quality facilities. Significant differences also existed among polytechnics in North, East, Central and South zones. All six service quality factors were linearly correlated and significant with levels of students’ satisfaction, the strongest was for campus climate (r =. 774, p =. 0001). Five out of six service quality factors accounted for 66.2% of the variance in students’ satisfaction. This study had implications on both quality facilities and support services in polytechnics. Both tangible (quality of program, facilities, academic staff, support services, accessibility and location) and intangibles aspects (campus climate) were important in polytechnics. Administrators need to improve strategies aimed at achieving better students’ satisfaction emphasizing both tangible and intangible aspects and responding to the demand for skilled workers in a competitive economy.